A colorimetric assay for detection of 6-OH-BDE-47 using 6-OH-BDE-47-specific aptamers and gold nanoparticles - Kim, Un-Jung; Kim, Byoung Chan (ELSEVIER SCIENCE SA, 2017)
A colorimetric aptamer/gold nanoparticle (AuNP) sensor to detect 6-hydroxy-2,2 ',4,4 ' tetrabromodiphenyl ether (6-OH-BDE-47) was developed using AuNPs and a 6-OH-BDE-47-specific ssDNA aptamer. 6-OH-BDE-47 is mono hydroxyl-substituted form of a major congener (2,2 ',4,4 ' tetrabromodiphenyl ether, BDE-47) of the polybrominated diphenyl ethers (PBDEs), which are representative persistent organic pollutants (POPs) and are widely used brominated flame retardants( BFR). AuNPs coated with 6-OH-BDE-47-specific aptamers initially exhibited repulsion; however, the aggregation of AuNPs was induced upon the introduction of 6-OH-BDE-47, detaching the aptamers from the AuNPs due to strong interactions between the aptamers and the target. In the colorimetric assay, the color of the testing solution changed from red to blue according to the degree of AuNP aggregation, with a limit of detection in the region of parts-per-billion (ppb), and a dynamic range of detectionranging from 5 ppb to 1 ppm. This colorimetric assay was then repeated using paper that absorbed AuNPs covered with 6-OH-BDE-47-specific aptamers. Similarly, a color change was observed when the paper was exposed to 6-OH-BDE-47. Compared to conventional trace quantitative analysis methods, this paper-based colorimetric assay is advantageous for quick screening in the case of sudden spills of highly concentrated chemicals. (C) 2017 Elsevier B.V. All rights reserved.
Keywords: POLYBROMINATED DIPHENYL ETHERS; MAGNETIC PARTICLE IMMUNOASSAY; FLAME-RETARDANT CHEMICALS; BIOSENSORS; PBDES; AGGREGATION; EXPOSURE; SAMPLES